Islamic Civil Society in Indonesia: NU and Muhammadiyah’s Role in Democracy and Social Harmony - Aris Munandar; Andi Muh. Dzul Fadli; Triono Triono; Endang Susanti (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2026)
This study aims to analyze the role of Islamic civil society in maintaining social harmony and strengthening the future of democracy in Indonesia by highlighting the contributions of Nahdlatul Ulama (NU) and Muhammadiyah, the two largest Islamic organizations in the country. Employing a field research design and a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation involving organizational leaders, academics, and relevant sources. The analysis utilized a descriptive-analytical method grounded in the civil society theories proposed by Robert W. Hefner and Larry Diamond. The findings reveal that NU and Muhammadiyah play strategic roles in reinforcing democratic values, promoting tolerance, and sustaining social cohesion within Indonesia’s pluralistic society. NU, through the concept of Islam Nusantara, integrates Islamic teachings with local cultural values, while Muhammadiyah advances progressive Islam by emphasizing rationality, education, and social reform. Despite these contributions, Indonesian democracy continues to face significant challenges, including religious populism, identity-based politics, and shifting political dynamics. This study concludes that strengthening Islamic civil society is essential for preserving social stability and ensuring the long-term sustainability of democracy in Indonesia.